Osvaldo Sangiorgi e "O fracasso da matemática moderna" no Brasil - Silva, Viviane da (2007)
The objective of this research was to understand how Osvaldo Sangiorgi made an appropriation of the Morris Kline´s book named O Fracasso da Matemática Moderna , after 15 years of Modern Mathematics Movement MMM in Brazil and to identify the arguments in which he was based on forward the declared failure to continue divulgating the Modern Mathematics up to the 1980s. To reach this, we studied several thesis and dissertations about MMM and analysed some document´s from Osvaldo Sangiorgi´s Personal Archive APOS. These informations was complemented by documents from Acervo Histórico do Instituto Brasileiro de Edições Pedagógicas IBEP and a recorded interview done with Sangiorgi in 1988. The theorical methodologies considerations whe sustained by the following authors: Chartier (1991) who supported us on the appropriation concept comprehension; Prochasson (1998), Gomes (1998) and Alves (2003) that assisted us with the treatment with the APOS; Geertz (1989) who supported us on culture concept; Certeau (1982) who taugh us the historian work, Chevel (1990) and Julia (2001) which we discussed the concept of pertaining to school culture and the purposes of education, and Nóvoa (1992) that helped us with the teacher´s history of life. We evidenced that the impact of the book written by Morris Kline, sure made possible some openings for discution on possible corretions for the problems detected in the education of the Modern Mathematics in Brazil. Osvaldo Sangiorgi detached some positive points emerged with the Movement, between them: the mobilization of uncountable teachers in TV and in-classe courses, promoted by Grupo de Estudos do Ensino da Matemática GEEM and the student´s motivation showed on the participation in the Olimpíadas de Matemática. Considering these factors, among others, kept on spreending the Modern Mathematics until the 1980s, inserting, in this context, the application of this mathematics notions into the computer science